Validation of the Korean Version of the Nursing Profession Self-Efficacy Scale: A Methodological Study - Oh, Jina (Int J Environ Res Public Health, 2021)
Background: The Nursing Profession Self-Efficacy (NPSE) scale was developed to reflect the characteristics of nursing tasks. This study was conducted to validate the Korean version of the NPSE (K-NPSE) scale. Methods: The NPSE scale with nineteen items was translated into Korean after forward and backward translation according to Devellis’ guideline. For the exploratory factor analysis (EFA), 298 nurses participated and criterion-related validity and reliability were verified. For the confirmatory factor analysis (CFA), 218 other nurses participated. Content validity, criterion-related validity, and internal consistency reliability were examined. Additionally, construct validity was examined. SPSS and AMOS were used for the data analyses. Results: Nineteen items were selected after evaluating the content and cognitive validity and comprised three factors: “Professional (10 items)”, “Advocating (4)”, and “Caring (5)”. Construct validity was supported by the CFA. Criterion-related validity was supported by comparison with the General Self-Efficacy Test (r = 0.43, p < 0.001). Cronbach’s alpha of the K-NPSE was 0.93. Conclusions: Study findings indicate that the K-NPSE could be useful for assessing nurses’ self-efficacy. The K-NPSE may be used as a valuable reference for developing programs or policies that promote nursing professionals. It is expected that continued use of this scale in various clinical settings to further generalize and validate the scale.